2019
DOI: 10.1186/s12944-019-1079-3
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial progenitor cell transplantation attenuates lipopolysaccharide-induced acute lung injury via regulating miR-10a/b-5p

Abstract: Background Bone marrow-derived endothelial progenitor cells (EPCs) are shown to attenuate lipopolysaccharide- (LPS-) induced acute lung injury (ALI) in animal models. However, the molecular mechanism is largely unknown. Materials and methods The animal model of ALI was induced by intratracheal instillation of purified LPS with 2.5 mg/ml/kg. The expression of microRNAs and ADAM15 in lung tissues and LPS-induced mouse pulmonary microvascular endothelial cells (MPMVECs) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…4e). Coexpression of α7nAChR and VE-cadherin was found in the periphery of blood vessels or capillaries in the bone It has been reported that EPC transplantation could improve LPS-induced acute lung injury [27,[39][40][41]. In 23 patients with pneumonia, the proportion of EPCs in peripheral blood MNCs was increased.…”
Section: Discussionmentioning
confidence: 97%
“…4e). Coexpression of α7nAChR and VE-cadherin was found in the periphery of blood vessels or capillaries in the bone It has been reported that EPC transplantation could improve LPS-induced acute lung injury [27,[39][40][41]. In 23 patients with pneumonia, the proportion of EPCs in peripheral blood MNCs was increased.…”
Section: Discussionmentioning
confidence: 97%
“…miRNAs inhibit translation or induce the degradation of targeted mRNA by binding to the 3' untranslated region (UTR) [9]. Increasing number of evidences have proved that miRNAs associated with certain inflammatory lung diseases.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are endogenous small non-coding RNAs with a length of 21-23 nucleotides. miRNAs inhibit translation or induce the degradation of targeted mRNA by binding to the 3' untranslated region (UTR) [12]. Increasing number of evidences have proved that miRNAs associated with certain in ammatory lung diseases.…”
Section: Introductionmentioning
confidence: 99%